Leaf cuticle in Brazilian species of Cryptocarya (Lauraceae) - Moraes, Pedro Luís Rodrigues De; Lauand Ribeiro, Henrique; Moysés Neto, Carlos Alberto (Phytotaxa, 2022)
In this study, we analysed leaf cuticle characters of 61 collections from 13 Cryptocarya species recognised in Brazil, of which 11 are considered endemic, and one Costa Rican collection of an unidentified species. Most Cryptocarya species studied have predominantly undulate anticlinal epidermal walls on the adaxial surface, butterfly-shaped stomatal ledges and the stomatal complex protruding and arching over the stomatal slit with a rim resembling two kidneys facing each other (reniform rims). Analysis of a matrix of six leaf cuticle qualitative characters and 19 states, most of them illustrated here for the first time by light and scanning electron microscopy, allowed us to distinguish these taxa. Based on these characters, two Brazilian Cryptocarya species can be easily separated from the others by their predominantly straight anticlinal epidermal walls adaxially and the almost flat surface appearance of the stomatal complex.